Sperm Cryopreservation in Canaries to Protect Endangered Songbird Species: Comparison of Different Cryoprotectants - Arda Onur Özkök; Burcu Esin; Eser Akal (Veterinary Medicine and Science)
ABSTRACT Sperm cryopreservation is a rather complex process that needs to be adapted to wild and domestic bird species to ensure adequate efficiency. This study aimed to determine the usability of different cryoprotectants in the cryopreservation of Gloster canary sperm. For this purpose, sperm samples were collected from 12 2‐year‐old male Gloster canaries three times a week using cloacal massage for 4 weeks. After individual evaluation, sperm samples from the canaries were combined. Mixed sperm were divided into two groups in the study. Overall, 8% dimethyl sulfoxide (DMSO) and ethylene glycol (EG) were used as cryoprotectants. Sperm samples were drawn into straws after adding Dulbecco's Modified Eagle Medium (DMEM) extender with high glucose ratio and two different cryoprotectants in a 1:1 ratio and frozen to −80°C with liquid nitrogen vapour and then stored in liquid nitrogen at −196°C. Frozen‐thawed semen samples were evaluated regarding motility, vitality, plasma membrane integrity (hypoosmotic swelling test [HOST]), density and abnormal spermatozoa rate. The highest motility value after freezing and thawing was determined in the EG group with 31.667% ± 4.773%. In addition, vitality, plasma membrane integrity and normal sperm morphology were statistically significantly higher in the EG‐frozen group, whereas head and tail abnormality was low (p < 0.05). This study determined that a DMEM extender containing 8% EG was more advantageous than a DMEM containing DMSO regarding spermatological parameters and could be used for long‐term storage of canary sperm.